Representation of lexemes ‘head’ / ‘bash’, ‘heart’ / ‘churek’ and ‘tongue’ / ‘dyl’ in Russian and Tuvan phraseological units - Denisenko, Anastasia V.; Kalinina, Yulia M. (The New Research of Tuva, 2023)
The article presents a linguoculturological analysis of lexemes ‘head’ / ‘bash’, ‘heart’ / ‘churek’, ‘tongue’ / ‘dyl’ which are significant for the Russian and Tuvan languages. Currently, there are a number of studies that consider these lexemes separately, but there is no comparative analysis of their occurrences in Russian and Tuvan. Therefore, the purpose of the article is generalizing the present variants of the representation of these lexemes, describing their role in phraseological units as exponents of ethnic mentality and conducting a comparative analysis of the functioning of these units in the Russian and Tuvan languages. The achievement of this purpose implies solving the following tasks: to identify Russian and Tuvan phraseological units with the components ‘head’ / ‘bash’, ‘heart’ / ‘churek’, ‘tongue’ / ‘dyl’ in lexicographic works, to determine the features of ethnic mentality expressed by these lexemes, as well as the similarities and differences of their representation in the languages compared according to the principle of division into: phraseological units that completely coincide in meaning with Russian phraseological locutions; phraseological units that partially correlate with Russian fixed phrases; phraseological units that have no analogues in the Russian language.The linguistic material studied and described in the article allows us to draw the following conclusions: a comparative study of phraseological units with lexemes ‘head’ / ‘bash’, ‘heart’ / ‘churek’, ‘tongue’ / ‘dyl’ shows that in the Russian and Tuvan languages there are phraseological units that coincide in meaning and may differ in structure; in Russian, compared with Tuvan, phraseological units with positive or negative connotations are more common; lexemes ‘head’ / ‘bash’, ‘heart’ / ‘churek’, ‘tongue’ / ‘dyl’ are the key ones in the compared languages as they are part of a large number of phraseological units and allow describing the main features of ethnic mentality.The authors of the article see the prospects for research in expanding the range of lexemes that are part of semantic field ‘person’ and describe the features of ethnomentality through representation in phraseological units.
Keywords: head; heart; language; phraseological unit; linguoculturological analysis; Tuvan language; Russian language